2023
DOI: 10.1002/adfm.202302444
|View full text |Cite
|
Sign up to set email alerts
|

Se‐Induced Fibrous Nano Red P with Superior Conductivity for Sodium Batteries

Abstract: Red phosphorus shows great promise as a high‐capacity anode material for Na batteries. Such electrodes that suffered from the fracturing impact of volume change during cycling can be effectively improved by 1D nanomaterials. However, the synthesis of 1D red phosphorus has rarely been studied and employed in sodium batteries. Here, a simple selenium‐induced method to generate fibrous nano red phosphorus is presented. It turns out that a small amount of selenium can not only induce high‐quality fibrous nano red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As an allotrope of red phosphorus, the FP with a regular crystal structure has a significantly increased electronic conductivity (approximately 10 8 times), which shows great prospects for improving the Na/K storage performance of the P-based anode materials. Recently, Zhu et al found that trace amounts of selenium (Se) could induce the conversion of commercial RP into crystalline FP and developed a 1D FP nanostructure via a typical annealing procedure (Figure 5d) [50]. As shown in Figure 5e, the as-prepared FP exhibits a typical morphology of nanofibers with a diameter of ~100 nm and length of 2-3 µm.…”
Section: D Materials: Nanowires Nanorods Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…As an allotrope of red phosphorus, the FP with a regular crystal structure has a significantly increased electronic conductivity (approximately 10 8 times), which shows great prospects for improving the Na/K storage performance of the P-based anode materials. Recently, Zhu et al found that trace amounts of selenium (Se) could induce the conversion of commercial RP into crystalline FP and developed a 1D FP nanostructure via a typical annealing procedure (Figure 5d) [50]. As shown in Figure 5e, the as-prepared FP exhibits a typical morphology of nanofibers with a diameter of ~100 nm and length of 2-3 µm.…”
Section: D Materials: Nanowires Nanorods Nanofibersmentioning
confidence: 99%
“…[42][43][44], copyright 2018, 2020, 2021, American Chemical Society; from Refs. [45][46][47][48][49][50], Copyright 2019, 2021, 2023, Wiley-VCH; from Ref. [51], Copyright 2021, Elsevier; from Refs.…”
Section: Characteristics and Challengesmentioning
confidence: 99%
“…Another alloy-type element is phosphorus with a weak electronegativity and high reactivity. Generally, phosphides can provide fast reaction kinetics, high coulombic efficiency, and reduced polarization for rechargeable batteries. In particular, the cubic SiP phase possesses a sphalerite lattice structure akin to the diamond lattice of silicon. Moreover, it can attain metallic conductivity, as confirmed by the calculated electronic structure (Figure S1), owing to the delocalized electrons introduced by phosphorus.…”
Section: Introductionmentioning
confidence: 99%